2006
DOI: 10.1108/02635570610688850
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for measuring KM performance outcomes in organisations

Abstract: PurposeThis research attempts to comprehensively examine the criteria for measuring knowledge management (KM) performance outcomes in organisations. To date, no studies have provided a set of widely accepted measurement criteria associated with KM efforts. This paper, therefore, aims to fill the gap.Design/methodology/approachThis study was carried out by systematically reviewing the literature on KM performance outcomes. Case studies were carried out in two organisations identified to have a KM programme in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(16 citation statements)
references
References 38 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Valuable novel knowledge is often generated and transformed into processes, services and products by changing the general knowledge into specific ones that benefits the organization (Siong, Kuan Yew, & Lin, 2006). For instance, Massey, Montoya-Weiss and O'Driscoll (2008) argued that proper implementation of KMS can innovative process.…”
Section: Knowledge Management Capacity and Intellectual Capital As Mementioning
confidence: 99%
“…Valuable novel knowledge is often generated and transformed into processes, services and products by changing the general knowledge into specific ones that benefits the organization (Siong, Kuan Yew, & Lin, 2006). For instance, Massey, Montoya-Weiss and O'Driscoll (2008) argued that proper implementation of KMS can innovative process.…”
Section: Knowledge Management Capacity and Intellectual Capital As Mementioning
confidence: 99%
“…As noted by several scholars, the outcomes of an effective information and knowledge management system can enhance work efficiency, reduce time in project coordination and paper documentations, which in turn will reduce operating and administrative expenses (Davenport, 1998;Emanuele et al, 2004). The findings obtained through both survey and personal interviews further affirmed the empirical findings of positive relationships between OL practices and business performance (Alavi and Leidner, 2001;Calantone et al, 2002;Sabherwal and Becerra-Fernandez, 2003;Lopez et al, 2005;Choy et al, 2006). In addition, this finding also implied the need to enhance the skills and knowledge of organizational members for effective utilisation of the computerised networks and knowledge management systems.…”
Section: Organizational Learning Practicesmentioning
confidence: 54%
“…The findings further suggest that ICT practices can improve financial performance only when they are coupled with HRM practices. Choy et al (2006) identified 38 items for measuring KM outcomes from a literature review. The authors grouped these items into the following five dimensions: Systematic knowledge activities; employee development; customer satisfaction; good external relationships and organisational success.…”
Section: Km and Organizational Performancementioning
confidence: 99%
“…We grouped the benefits mentioned in the papers on the basis of the five dimensions proposed by Choy et al (2006). It is evident that small businesses can substantially benefit from applying knowledge management initiatives.…”
Section: Studies Involvedmentioning
confidence: 99%
See 1 more Smart Citation